The Influence of Sowing Date and Norms on the Yield of "Madad" Variety of Soybean - L.Kh. Dusmatova,; B.M. Khalikov (Zien Journals, 2022)
This article presents data on the influence of sowing period and norms of soybean variety "Madad" on the grain yield in the conditions of meadow-swamp soils of Tashkent region. According to the data, sowing of this variety early, in the period of 25.04-30.04 at the rate of 60 kg per hectare, was the highest indicator among the options, 32.3 c/ha. In this case, the additional yield from soybeans was 1.2-3.8 c/ha according to sowing dates, and 0.6-2.8 c/ha according to sowing norms.
Keywords: Soybean; variety; seed; plant